Strategies for drug delivery to the human inner ear by multifunctional nanoparticles. (January 2012) - Roy, Soumen; Glueckert, Rudolf; Johnston, Alex H; Perrier, Thomas; Bitsche, Mario; Newman, Tracey A; Saulnier, Patrick; Schrott-Fischer, Anneliese
Hearing loss is a very significant health problem. The methods currently available for inner ear drug delivery are limited and a noninvasive cell-specific drug delivery strategy needs to be found.Aim: In this study we investigated the ability of polymersomes, lipid core nanocapsules and hyperbranched poly-L -lysine to cross the round window membrane.Materials & Methods: Nanoparticles (NPs) used in this study have different size and chemical compositions. Freshly frozen human temporal bones were used for this investigation. Intact human round window membrane within the freshly frozen human temporal bone served as an excellent model to test the membrane permeation and distribution within the tissues.Results: In this investigation we were able to visualize the NPs across the round window membrane. The NPs were subsequently found to be distributed in the sensory hair cells, nerve fibers and to other cells of the cochlea.Conclusion: This finding raises hope in terms of future multifunctional NP-based drug delivery strategy to the human inner ear.